Analisis Historis Manajemen Dakwah Rosulullah Saw dalam Piagam Madinah - Ridwan Rustandi; Syarif Sahidin (IAIN Syekh Nurjati Cirebon, 2019)
AbstractThis study aims to explore the values of the peace negotiations contained in the Medina charter as part of the management of the missionary Rasulullah Saw. Negotiations are an alternative method of Islamic da'wah carried out by paying attention and considering various socio-cultural-political conditions. One of the peace talks that was carried out by Rasulullah Saw who was laden with the values of Islamic da'wah was the Medina Charter. This research uses a qualitative approach that is carried out through the content analysis method. The study was conducted by searching the literature to collect data related to the research topic. The results showed that the peace negotiations in the history of Islamic da'wah were carried out by Rasulullah Saw as a form of missionary management with an orientation to reach an agreement and embody social cohesiveness. The Medina Charter as a peace treaty contains various values that can be applied in social life including 1) the value of tolerance as a social glue; 2) the value of humanity as a foundation; 3) the value of God (transcendence) as the foundation of life; and 4) the value of liberation as a manifestation of creation. These four values have a strong significance in the context of contemporary da'wah, especially in dealing with the potential for conflict in society.